Harmonizing Child-Friendly Early Childhood Education: The Impact of Gamelan Music on Focus and Attention in Child-Centric Learning Environments - Al Baqi, Safiruddin; Puspitasari, Ratna Nila (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Focus and attention are very important abilities for children to train because they will affect various aspects of their future lives This study aims to explore the influence of gamelan music on young children's focus during cutting and pasting activities. Using the experimental method, the number of participants was 30 children (12 boys and 18 girls) with a mean age of 5.54 years (SD: 0.50). The research subjects were divided into two groups, namely the experimental group who were given galeman music and the control group who were not given. . The results of the study showed that children who were given gamelan music while carrying out these activities tended to have lower levels of concentration. These findings highlight the importance of paying attention to the auditory environment when designing early childhood learning experiences. Gamelan music, with its distinctive sound characteristics, can be a distractor that affects a child's ability to focus on a given task. Therefore, the recommendation to carefully select the type of music played in the background in early childhood learning activities is necessary to support their cognitive development optimally.